KEYAKINAN DAN KESEDIAAN MICRO MERCHANT MEMBAYAR SETTLEMENT EXPENSE DAN MERCHANT DISCOUNT RATE PENGGUNAAN QRIS UNTUK MENINGKATKAN SUSTAINABILITY REPORTING PADA COFFEE SHOP DI KARAWANG - Aulia, Aulia Nur Endayani; Lukita, Carolyn; Arimurti, Trias (JURNAL KINDAI, 2024)
This research aims to find out how confident and willing Micro, Small and Medium Size Enterprises (MSMEs) are to pay the settlement and Merchant Discoount Rate (MDR fees for using QRIS at micro merchant coffee shops in Karawang to improve their business sustainability reports. This research used descriptive and narrative qualitative methods, as well as interview, observation, and documentation data collection methods. The scope of the research focuses on micro-merchants in the Food and Beverage (FnB) Coffee Shop sector, the research locus in Karawang, with the number of coffee shops taken being 4. The results of this research explain that micro-merchant coffee shops in Karawang are confident and willing to pay settlement fees and merchant discount rates set by Bank Indonesia. Currently, there is minimal research that addresses the theme of confidence and the willingness of micro merchants to pay the settlement and MDR fees on QRIS to improve business sustainability reports. Researchers hope this research can become research literature material for MSMEs that have implemented QRIS in their business and Bank Indonesia. This research can be a consideration in determining settlement fees and MDR in an absolute and fair manner, both for merchants and their business customers. Keywords: QRIS, Settlement Fees, MDR, Sustainability Report, Merchant